Biochar-based contaminant removal: A tutorial on analytical quality assurance and best practices in batch sorption - Tellulah A. Fernando; Dinushi N. Fernando; Sameera R. Gunatilake; Chanaka Navarathna; Xuefeng Zhang (Journal of Chromatography Open)
Biochar, a biomass-derived, ubiquitous, porous, carbonaceous material that is rich in surface functional groups, is a research frontier in water remediation due to its sustainability and efficacy. The accuracy and the reliability of laboratory scale biochar-based batch sorption experiments are essential for a successful transition to pilot scale applications. The accuracy in preparation of solutions, proper storage conditions, and selection of the most appropriate instrumental method and its corresponding sensitivity, selectivity, detection limits and repeatability should be assessed to ensure analytical quality assurance (QA) during the quantification of analytes. A comprehensive batch sorption study involves optimizing sorption parameters and conducting kinetic studies, isotherm fitting, regeneration studies, competitive sorption experiments, and evaluating remediation in a real water matrix. Moreover, sorption parameters such as the pH, and contact time, should be optimized through iterative adjustments utilizing standard procedures to avoid erroneous assessments. Biochar-based sorption studies are conducted by scientists from various disciplines; thus, there is a propensity to overlook the above-mentioned factors which can impact the credibility of results. This tutorial aims to bridge this gap by expounding analytical QA and best practices in batch sorption experiments, ensuring accuracy to obtain reliable results and conclusions.